Connecting community‐delivered evidence‐based programs and the healthcare system: Piloting a learning "wellcare" system - Sarah Redmond; Aaron L. Leppin; Karen Fischer; Gregory Hanson; Chyke Doubeni; Paul Takahashi (Wiley, 2021)
Abstract Introduction Many evidence‐based programs (EBPs) have been determined in randomized controlled trials to be effective, but few studies explore the real‐world effectiveness of EBPs implemented in the natural community setting. Our study evaluated whether a novel linked infrastructure would enable such insights and continuous improvement as part of a learning healthcare‐community bridged "wellcare" ecosystem. Methods We created a secure, web‐based data entry and storage platform with a network of Minnesota community‐based organizations to record EBP participants' demographics and attendance, and program details. We then linked participant's information to their Rochester Epidemiology Project (REP) medical records. With this infrastructure, we conducted a proof of concept, retrospective cohort study by matching EBP participants to REP controls and comparing medical record‐documented outcomes over 1 year follow‐up. Results We successfully linked EBP participant records with medical records in 77.6% of cases, and the infrastructure proved feasible and scalable. Still, key challenges remain in obtaining participant consent for data sharing. Upfront resource investments and the availability of REP‐like warehouses limit generalizability. Optimal learning will be improved by enhancements that better track program fidelity. Our pilot study established a proof‐of‐concept, but sample sizes (n = 99 for falls prevention and n = 97 chronic disease/pain management EBP completers) were too small to detect significant differences in hospital admittance as compared to matched controls for either EBP group, (OR = 0.66[0.36, 1.19]) and (OR = 0.81[0.43, 1.54]), respectively. Events were too rare to gather meaningful information about effects on fall rates. Conclusions Our pilot demonstrates the feasibility of developing an online infrastructure that connects information from community leaders with medical record documented health outcomes, bridging the knowledge gap between community programs and the health care system. Insights gleaned from our infrastructure can be used to continuously shape community program delivery to reduce the need for formal health care services.